A LINGUISTIC ANALYSIS OF HIGHER EDUCATION TERMINOLOGY DERIVED FROM THE UZBEK LANGUAGE - Lobar Saidnabiyeva (Bright Mind Publishing, 2025)
This article is devoted to the linguistic analysis of higher education terminology formed in the Uzbek language, focusing on their origins, methods of formation, and practical usage. The author emphasizes the intrinsic connection between the development of the higher education system and the evolution of language and terminology, highlighting the role of Uzbek-language terms in shaping the foundations of the national education system. The study classifies higher education terms according to their sources, including native Uzbek lexicon and borrowings from Russian, English, Arabic, and Persian. It examines derivational processes such as affixation, calquing, semantic extension, compounding, and phonetic adaptation. The article also addresses key challenges such as synonymy, instability, and improper adaptation of terms. Furthermore, it offers recommendations for the standardization of terminology and its integration into contemporary scientific discourse. In conclusion, the article argues that higher education terms in Uzbek function not only as linguistic units but also as significant markers of national identity and educational policy.
Keywords: terminology, synoymy, affxation, doicourse, semantic, term, literary language.